Analysis of the tourism-economy-ecology coupling coordination and high-quality development path in karst Guizhou Province, China - Gui Meng; Kaiyong Wang; Fuyuan Wang; Yaojia Dong (Ecological Indicators, 2023)
Developing tourism is conducive to stimulating the vitality of regional economic development, improve economic backward areas of people's living standards. However, the development of tourism often brings great negative impact on regional sustainable development, especially in ecologically fragile areas. Therefore, the main purpose of this article is to identify the spatial changes of tourism-economy-ecological (TEE) system development in ecologically fragile areas of southwest China and promote the coordinated development of the system. Based on the entropy weight method, coupling coordination degree (CCD) model and obstacle degree model, this article focuses on the analysis of the development level, coupling coordination status and related obstacle factors of the TEE system in prefecture cities of Guizhou Province from 2009 to 2021. This result shows that: (1) Guizhou Province has made remarkable progress in environmental governance, however, the comprehensive development level of tourism system in most cities was relatively low, and obviously lagged behind the comprehensive development of economy and ecology. (2) The CCD level of each city had been continuously improved from 2009 to 2021. Cities with low coupling coordination in 2009 showed a relatively high rate of improvement in later period. (3) The obstacle factors affected harmonious development changed from the low number of domestic tourists and low tourism income in 2009 to insufficient number of travel agencies and star-rated hotels in 2019, and to the sharp decline of international tourists and tourism foreign exchange income in 2021. (4) The impact of COVID-19 on the harmonious development in TEE system, was relatively controllable. Nowadays, the ecological environment of most cities in Guizhou Province maintains a steady improvement trend, but the development of tourism lags behind and the lack of economic growth momentum is a serious problem. Based on the above analysis, tourism should be stimulated within the carrying capacity of ecological environment, and enterprises with development potential should be invited for investment and production in the future. Targeted policies should be formulated according to regional development differences, such as mountain tourism and ethnic culture tourism in the western mountainous area of Guizhou Province, while the eastern ecologically sound areas should pay more attention to the investment and management of ecological environment, attach importance to the construction of tourism infrastructure, improve the service level, and constantly enhance the quality of tourism development. These conclusions can also provide relevant experience and reference for realizing high quality economic development in other ecologically fragile areas.